Tidal Effects on the Schumann Resonance Amplitudes Recorded by the Global Coherence Monitoring System - Ugnė Orinaitė; Darius Petronaitis; Arvydas Jokimaitis; Mantas Landauskas; Minvydas Ragulskis; Alfonsas Vainoras; Rollin McCarty; Mike Atkinson; Nachum Plonka (Applied Sciences, 2024)
The main scientific result of this paper is the demonstration of the fact that tidal effects induced by the Moon affect the Schumann resonance amplitudes measured at magnetometers located at different geographical locations of the Global Coherence Monitoring System. Each magnetometer is paired with the closest monitoring station of the global tidal wave measurement network. This paper introduces the Schumann Resonance Complexity Index (SRCI), computed by using the calibrated H-rank algorithm on the local magnetic field data recorded by each magnetometer of the Global Coherence Monitoring System. Tidal wave data recorded at each monitoring station are also used to compute the Tidal Wave Complexity Index (TWCI). Eliminating diel cycles from the SRCI data yields significant statistical correlations between the SRCI and TWCI data, proving the hypothesis of tidal effects on the global network of magnetometers.